From Marshallian Citizenship to Corporate Citizenship: The Changing Nature of Citizenship in Neoliberal Britain - Emma Bell (Revue Française de Civilisation Britannique)
Whilst traditional definitions of citizenship, such as that of T.H. Marshall, have tended to emphasise the relationship between individuals and the State, over the past twenty years or so a new definition of citizenship has become popular which has instead highlighted the relationship between corporations and civil society. The notion of ‘corporate citizenship’ seems to have replaced that of ‘corporate social responsibility’ to outline the key duties that corporations owe to society, namely being profitable, obeying the law, engaging in ethical behaviour and philanthropic endeavours. Yet, this paper seeks to argue that, in adopting the term ‘citizenship’, with all its connotations of reciprocity, corporations also seek to lay claim to certain rights from the state. The corporate citizen may thus appear to be very similar to the individual citizen in terms of the rights it may claim from the state in return for exercising duties to civil society. But in practice the corporate citizen is accorded a special citizenship status, acting in partnership with government to deliver certain rights and to determine who may have access to citizenship. As a result, the very concept of social citizenship as defined by Marshall is altered: citizenship is no longer seen as primarily rights-based, as more emphasis is placed on duties; citizenship is no longer universal as some citizens are seen to be more equal/deserving than others; most importantly, citizenship is no longer defined exclusively vis-à-vis the state, leading to serious problems of accountability.